Canopy Temperature as a Water Stress Indicator in Vines - Van Zyl, J.L. (South African Journal of Enology and Viticulture, 2017)
Canopy temperature (CT) of vine plots subjected to drying cycles, and of well-watered control plots was measured with the aid of an infra-red thermometer in a full-bearing Colombar vineyard together with measurements of leaf water potential (LWP) and stomata) resistance (Rs). A decrease in transpiration rate due to water stress caused plant temperature to rise above that of the non-stressed control. A maximum temperature difference of 3,2°C was obtained. The infra-red thermometer proved itself accurate and facilitated rapid temperature determinations while measurements of CT integrated temperatures of individual leaves. Canopy temperature was significantly and linearly correlated with soil water content (SWC). The study indicated that the onset of vine water stress occurred at plant available water contents of 30% - 50%, coinciding with a CT increase of 1,l6°C - 1,62°C above that of the control.